THE ROLE OF GENETIC POLYMORPHISMS OF GENE IL-1β (-31 Т/С) AND IL-6 (-174 G/C) IN THE COURSE OF CHRONIC HEPATITIS B AND C IN CHILDREN - S. V. Romanova; Т. А. Vidmanova; Е. А. Zhukova; Е. V. Ermolina; N. I. Tolkacheva; I. V. Mayanskaya; I. А. Timchenko (Медицинская иммунология, 2014)
Abstract. Objectives: Chronic viral hepatitis В (CHB) and С (CHC) comprise an important issue of modern pediatrics. Immunogenetic disorders are among key factors of their pathogenesis. The aim of present research was to reveal interactions between polymorphisms of cytokine IL-1β and IL-6 genes and clinical characteristics of the disease in children.The study included forty-eight children aged from 6 to 17 years (a median of 12 years old), including thirty patients with CHC, and eighteen – with CHB. Polymorphism of cytokine genes – interleukin 1β (IL-1β) – T31C, interleukin 6 (IL-6) – G174C was evaluated by means of allele-specific polymerase chain reaction (PCR); the amplification products were detected by horizontal electrophoresis (“Litekh”, Russia).The groups of CHB and CHC patients were characterized by increased prevalence of CC genotype of IL- 1β Т/С -31gene and СС genotype of IL-6 -174 G/C gene variants, as compared to control group [OR = 3.66 (95% CI – 1.2-11.0) and OR = 2.81 (95% CI – 1.33-5.87)]. The IL-6 -174 G/C polymorphism of is associated with higher IL-1β synthesis in GG genotype carriers, when compared to GC (p = 0.016) and СС genotypes (p = 0.030). In children with active CHB and CHC, polymorphisms of IL-1β -31 ТС and СС, as well as IL-6 -174 СC, were related to the higher cytolysis level, while the genotypes IL-1β -31 ТТ and IL-6 -174 GC and GG – with absence of cytolytic features(p = 0.022; p = 0.038).Presence of polymorphisms of IL-1β and IL-6 genes may sufficiently contribute to susceptibility to chronic hepatitis development and have an impact on extent of clinical and immunological presentations of the disease.